2011
DOI: 10.1016/j.cub.2011.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Introgression of Anticoagulant Rodent Poison Resistance by Hybridization between Old World Mice

Abstract: Summary It is known that evolution by selection on new or standing single nucleotide polymorphisms (SNPs) in the vitamin K 2,3-epoxide reductase subcomponent 1 (vkorc1) of house mice (Mus musculus domesticus) can cause resistance to anticoagulant rodenticides such as warfarin [1–3]. Here we report an introgression in European M. m. domesticus spanning as much as ~20.3 megabases (Mb) and including vkorc1, the molecular target of anticoagulants [1–4], that stems from hybridization with the Algerian mouse (M. spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
375
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(410 citation statements)
references
References 30 publications
19
375
1
9
Order By: Relevance
“…The combination of R12W, A26S, and A48T in exon 1 associated with the R61L mutation in exon 2 was previously described as the Vkorc1 spr genotype (Song et al., 2011). However, other mutations were found to be present on the same allele of Vkorc1 .…”
Section: Resultsmentioning
confidence: 99%
“…The combination of R12W, A26S, and A48T in exon 1 associated with the R61L mutation in exon 2 was previously described as the Vkorc1 spr genotype (Song et al., 2011). However, other mutations were found to be present on the same allele of Vkorc1 .…”
Section: Resultsmentioning
confidence: 99%
“…For adaptive introgression to occur, a beneficial mutation should cross the species barrier through a rare hybridization event and overcome any fitness cost incurred from hybrid incompatibilities. The most well-characterized animal examples include warfarin resistance in European house mice (36) and melanism in North American gray wolves (37). Adaptive introgression of an insecticide-resistance gene between A. gambiae and A. coluzzii has been reported in numerous papers (12,19,(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed several mechanisms, including introgression, that can lead to adaptive divergence, especially in rapidly radiating groups (Pease et al 2016). There are numerous striking examples of adaptive introgression in plants, animals and humans that illustrate functional introgressed loci contributing to ecologically and reproductively significant traits (Whitney et al 2006; Song et al 2011; Sankararaman et al 2014; Lamichhaney et al 2015). Epichloë spp., grass endophytes in Hypocreales, contain many species that have evolve through a complex process of hybridisation (Moon et al 2004), indicating there is high possibility for the occurrence of introgression.…”
Section: Introductionmentioning
confidence: 99%